(3YbO GdOQQ aj TQM eNJUQ fNHI GdacQs - (3eMehO TcQj Hf YHO Gddg HgGAGdOjf Hf CHj GdKfGA TgGH GdOjf GdMSjfj GdBdhSj GdHZOGOjs; (3GdWfWGhj , YHO GdhgGH Hf CMeO Hf HQcGJ GdCMeOjs ((3UGdM Hf eMeO Hf jhSa s)
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ Edi Gddg JYGdi GdSjO eMehO TcQj GdCdhSj GdHZOGOj Ef CMb GdYdhe HGdJbOjeGdETJZGd HYde GdMOjK s
(3BNQgG (B:s
(3hMSf GdCOH aj eYGedJc hGdQVG dbVGFc hdGMhd hdGbhI EdG HGddg GdYdj GdYXje hUdi Gddg JYGdi hSde Ydi SjOfG eMeO GdQDa GdQMje s
(3GdfSNI HgG MhGTs
(3HChdgG Jedc jQLY dSfI (B1346 (3g`s
(3fNHI GdacQ ai eUWdM Cgd GdCKQ ddMGaX TgGH GdOjf Hf MLQ GdYSbdGfi cTa GdXfhf L (B2 (3U (B1936 s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs